1995
DOI: 10.1007/bf00964120
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricle haemodynamics and vaso-active hormones during graded supine exercise in healthy male subjects

Abstract: Left ventricle systolic and diastolic functional parameters were measured by gated equilibrium radionuclide cardiography in 12 healthy men (age 33-51 years) at rest and during graded supine exercise. The leftventricle end-diastolic volume showed an initial small (11%) increase during low submaximal exercise [from mean 163 (SD 40) at rest to mean 181 (SD 48) ml], while left ventricle end-systolic volume decreased successively [from mean 59 (SD 19) to mean 39 (SD 21) ml] with increasing exercise. Stroke volume w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…However, the percentage change in SV from rest to maximum upright exercise was substantially larger than that observed during supine exercise. Investigators have shown that there are minor changes in SV during incremental exercise in the supine position in healthy individuals (Kanstrup et al 1995). The results from the present investigation indicate that the myocardium may approach its limits for ventricular filling during supine exercise.…”
Section: Supine Versus Upright Exercisesupporting
confidence: 48%
See 1 more Smart Citation
“…However, the percentage change in SV from rest to maximum upright exercise was substantially larger than that observed during supine exercise. Investigators have shown that there are minor changes in SV during incremental exercise in the supine position in healthy individuals (Kanstrup et al 1995). The results from the present investigation indicate that the myocardium may approach its limits for ventricular filling during supine exercise.…”
Section: Supine Versus Upright Exercisesupporting
confidence: 48%
“…These investigators commonly reported an initial increase in EDV followed by a sharp decline at maximal exercise. A consecutive decline in end-systolic volume has also been commonly observed during incremental exercise (Adams et al 1992;Kanstrup et al 1995). Others have reported maintenance of EDV throughout incremental exercise, with a concomitant reduction in end-systolic volume (Jensen-Urstad et al 1998).…”
Section: Stroke Volume Response To Exercisementioning
confidence: 89%
“…[32][33][34][35] Moreover, previous studies have indicated that ventricular function indexes (LVEF, LVFS, or left ventricle volume) increased significantly during upright exercise in healthy humans (vs. the resting state) and that plasma catecholamine concentrations were positively correlated with LVEF changes or left ventricle volume. [36,37] However, the resting LVEF value decreased significantly after metoprolol treatment for coronary artery disease, [38] and children with vasovagal syncope experience symptom improvement after metoprolol treatment. [39] The above facts attracted us to design the present study to evaluate if LVEF might be associated with symptom improvement after metoprolol treatment for children and adolescents with POTS.…”
Section: Discussionmentioning
confidence: 99%
“…the resting state) and that plasma catecholamine concentrations were positively correlated with LVEF changes or left ventricle volume. [ 36 , 37 ] However, the resting LVEF value decreased significantly after metoprolol treatment for coronary artery disease, [ 38 ] and children with vasovagal syncope experience symptom improvement after metoprolol treatment. [ 39 ] The above facts attracted us to design the present study to evaluate if LVEF might be associated with symptom improvement after metoprolol treatment for children and adolescents with POTS.…”
Section: Discussionmentioning
confidence: 99%